2013
DOI: 10.1002/ejoc.201300524
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Michael/Aromatization Reaction of Azlactones to α,β‐Unsaturated Pyrazolones with C‐4 Regioselectivity Catalyzed by an Isosteviol‐Derived Thiourea Organocatalyst

Abstract: Pyrazoles are an important class of molecular structures with significant biological and pharmaceutical activities. Herein, heterocyclic compounds containing both a pyrazole motif and a masked amino acid structure are synthesized through the asymmetric Michael/aromatization of azlactones to α,β‐unsaturated pyrazolones by using isosteviol‐derived amine thiourea as the organocatalyst. The products are obtained in good yields (up to 93 %) with good diastereoselectivities and good enantioselectivities (up to >10:1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…A bifunctional amine thiourea XXXI, derived from isosteviol catalyzed the enantioselective Michael addition of azlactones 107 to a,b-unsaturated pyrazolones 86 with complete C-4 regioselectivity (Scheme 41). 62 A series of heterocyclic adducts 108 bearing a pyrazole moiety and azlactone -a masked amino acid structure, was easily synthesized in good yields with moderate to high enantioselectivities and very good dr. The azlactone bearing an alkyl group at the R 2 position however failed to provide the desired product, even when using a higher catalyst loading of 30 mol% at room temperature.…”
Section: Addition To the B-carbon Of The Ab-unsaturated Pyrazolonesmentioning
confidence: 99%
“…A bifunctional amine thiourea XXXI, derived from isosteviol catalyzed the enantioselective Michael addition of azlactones 107 to a,b-unsaturated pyrazolones 86 with complete C-4 regioselectivity (Scheme 41). 62 A series of heterocyclic adducts 108 bearing a pyrazole moiety and azlactone -a masked amino acid structure, was easily synthesized in good yields with moderate to high enantioselectivities and very good dr. The azlactone bearing an alkyl group at the R 2 position however failed to provide the desired product, even when using a higher catalyst loading of 30 mol% at room temperature.…”
Section: Addition To the B-carbon Of The Ab-unsaturated Pyrazolonesmentioning
confidence: 99%
“…[33] In 2013, the Wang group reported that isosteviol-derived amine thiourea C19 catalyzed enantio-and diastereoselective conjugate addition of azlactones 68 to a,b-unsaturated pyrazolones 69, with exclusive C-4 regioselectivity (Scheme 17). [34] Azlactones 68 with aryl substituents at C-2 (R 1 = aryl) were converted to the conjugate adducts 70 in moderate to excellent yields, diastereo-and enantioselectivities. Surprisingly, the reaction was unsuccessful with alkyl-substituted 68 (R 1 , R 2 = alkyl) under these optimized reaction conditions.…”
Section: Asymmetric Michael Additionsmentioning
confidence: 99%
“…To go deep into the research on isosteviol, a large number of isosteviol derivatives have been obtained by microbial transformation and chemical modification. The typical properties of isosteviol derivatives, such as cytotoxic activities, catalytic performance, as well as supramolecular self‐assembly properties, were further investigated in recent years. Notably, some of the synthetic isosteviol derivatives exhibited remarkable inhibitory activity against cancer cells that captured scientific attention with possible applications in anticancer drugs design and development.…”
Section: Introductionmentioning
confidence: 99%